Affinity purification of cardiac adenylate cyclase: dependence on prior hydrophobic resolution. - Homcy, C (Proc Natl Acad Sci U S A, 1978)
The interaction of cardiac adenylate cyclase [ATP pyrophosphate-lyase (cyclizing); EC 4.6.1.1] with a variety of nucleotide affinity resins was systematically investigated. None of these resins effectively bound the native, detergent-solubilized enzyme. However, after hydrophobic resolution on an uncharged resin consisting of long-chain alkyl groups linked to agarose via ether bonds, 40% of the adenylate cyclase activity biospecifically adsorbed to an ATP affinity resin. Gel filtration without detergent after hydrophobic chromatography demonstrated that the enzyme eluted in the identical position as the native enzyme chromatographed in the presence of detergent. This preparation almost completely biospecifically adsorbed to the same ATP-resin and was not eluted with 5 mM cyclic AMP, pyrophosphate, or GTP. If the GTP-washed immobilized enzyme was subsequently desorbed with ATP, then expected Gpp(NH)p (5'-guanylyliminodiphosphonate) sensitivity persisted. A preliminary purification scheme that resulted in an approximate 5000-fold increase in specific activity is presented. These observations indicate that a membrane-bound enzyme may appear to be intrinsically hydrophobic only by virtue of aggregation with other hydrophobic constituents and that prior separation of hydrophobic chromatography may permit such proteins to be fractionated subsequently by methods conventionally applied to hydrophilic proteins.